Using Modern Management Accounting Applications To Reduce Costs - Rawaa Hussein Hameed (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research seeks to find an approach between modern trends in management accounting and cost reduction. The research problem was represented by a number of questions with the aim of identifying the intellectual and applied frameworks of its variables, and then diagnosing the level of interest in it in the field, as well as identifying the appropriate procedures by the company. Three main hypotheses were developed to measure the level of correlation and influence between the research variables. The research was conducted in Al-Enjaz Juice Manufacturing Company as a field for research and testing its hypotheses. The target cost method, the cost method based on activities, and the balanced scorecard method were adopted. The research used many statistical methods in the analysis, such as standard deviations, arithmetic averages, with the help of statistical programs (SPSS.var.29). A set of results was reached, the most important of which is the existence of a correlation relationship and the influence of modern management accounting applications in reducing costs